(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Because of its antioxidant and anti-amyloidogenic properties, Cassia tora Linn. being investigated in this research for its possible use in treating Alzheimer’s disease. We used ethanol and water as solvents to extract Cassia tora leaf powder after collecting, drying, and grinding the leaves. The suppression of amyloid-β (Aβ1-42) aggregation at different doses of the extracts was measured using the Thioflavin T fluorescence test to assess the anti-amyloidogenic activity. A one-way analysis of variance (p = 0.0023) confirmed that the extracts of Cassia tora inhibited amyloid aggregation in a dose-dependent manner. These results indicate that Cassia tora has promise as an antioxidant and natural agent with anti-amyloidogenic effects; hence, it might be used to control Alzheimer’s disease.